2014
DOI: 10.1590/abd1806-4841.20143176
|View full text |Cite
|
Sign up to set email alerts
|

High-frequency ultrasound associated with dermoscopy in pre-operative evaluation of basal cell carcinoma

Abstract: The recent development of high-frequency ultrasound, associated with the improved sensitivity in color Doppler, enabled the identification of various skin structures and layers. In basal cell carcinoma, the 22 MHz frequency ultrasound permits the delimitation of tumor margins, while color Doppler, determines its vascularization. We present two cases in which the association of both exams allowed an in vivo analysis of the tumor's morphology, size, thickness and vascularization, thus contributing to a better pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 9 publications
1
35
0
Order By: Relevance
“…A similar US picture of BCCs was described by Desai et al and Schmid-Wendtner et al who used the 20 MHz frequency probe and defined BCCs as alternating hypo-and hyperechoic areas, with no clear margins between the tumor and the perifocal infiltrate [11,12]. Other authors reported using the 22 MHz transducer and described BCC lesions as heterogeneous, hypoechoic formations in the dermis with a regular contour and large, hyperechoic internal signals [13]. In our study, we used the 75 MHz frequency probes for superficial and sclerodermiform BCCs and 30 MHz frequency probe for the nodular BCCs, that contributed to the more accurate visualization of the margins, sizes and structure of tumors.…”
Section: Discussionsupporting
confidence: 56%
“…A similar US picture of BCCs was described by Desai et al and Schmid-Wendtner et al who used the 20 MHz frequency probe and defined BCCs as alternating hypo-and hyperechoic areas, with no clear margins between the tumor and the perifocal infiltrate [11,12]. Other authors reported using the 22 MHz transducer and described BCC lesions as heterogeneous, hypoechoic formations in the dermis with a regular contour and large, hyperechoic internal signals [13]. In our study, we used the 75 MHz frequency probes for superficial and sclerodermiform BCCs and 30 MHz frequency probe for the nodular BCCs, that contributed to the more accurate visualization of the margins, sizes and structure of tumors.…”
Section: Discussionsupporting
confidence: 56%
“…In HFUS, skin cancer, malignant or benign, usually presents as hypoechoic areas in contrast to the adjacent healthy tissue. 18 , 27 In addition to echogenicity, it's possible to assess the lesion shape, the longitudinal, transverse and axial measures, the edges, the contour and the involvement of deep layers, such as muscle, cartilage and bone. 28 The study of the vascularization can be accomplished with the combination of color Doppler or power Doppler, which allows observing the distribution, size and nature (arterial or venous) of tumor vessels.…”
Section: Applicationsmentioning
confidence: 99%
“…The diagnosis of the skin cancer relies on clinical inspection, palpation, dermoscopy followed by incisional or excisional biopsy. With dermoscopy, it is possible to assess the extension of the lesion in the longitudinal and horizontal axes but not to determine its depth and the potential invasion of adjacent structures [5][6][7]. The American Joint Committee on Cancer (AJCC) staging system uses depth of invasion (DOI) in the staging of non-melanoma skin cancer which changes the staging in the case of an invasion greater than 6 millimeters.…”
Section: Introductionmentioning
confidence: 99%